2020
DOI: 10.3390/cancers12040798
|View full text |Cite
|
Sign up to set email alerts
|

External Beam Radiation Therapy and Enadenotucirev: Inhibition of the DDR and Mechanisms of Radiation-Mediated Virus Increase

Abstract: Ionising radiation causes cell death through the induction of DNA damage, particularly double-stranded DNA (dsDNA) breaks. Evidence suggests that adenoviruses inhibit proteins involved in the DNA damage response (DDR) to prevent recognition of double-stranded viral DNA genomes as cellular dsDNA breaks. We hypothesise that combining adenovirus treatment with radiotherapy has the potential for enhancing tumour-specific cytotoxicity through inhibition of the DDR and augmentation of virus production. We show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 61 publications
(91 reference statements)
3
9
0
Order By: Relevance
“…In vivo experiments using xenograft models in SCID mice showed an additive, and possibly a synergistic, effect when combining EnAd (hybrid of two group B adenoviruses-Ad3 and Ad11p) with low-dosage radiation. This study complements previous findings of OAd having the potential to serve as radiosensitizers [8].…”
supporting
confidence: 90%
See 1 more Smart Citation
“…In vivo experiments using xenograft models in SCID mice showed an additive, and possibly a synergistic, effect when combining EnAd (hybrid of two group B adenoviruses-Ad3 and Ad11p) with low-dosage radiation. This study complements previous findings of OAd having the potential to serve as radiosensitizers [8].…”
supporting
confidence: 90%
“…Moreover, they showed that Paclitaxel treatment synergistically enhanced the oncolytic activity of AdAREF (also known as Ad-fosARE) both in vitro and in vivo [6], and also demonstrated that the combination of adenovirus and Cisplatin increased cell killing and increased virus replication both in vitro and in vivo [7]. In terms of combination therapy, another interesting report in this issue by Pokrovska et al highlights the potential benefits of combining radiation therapy with oncolytic viruses [8]. In vivo experiments using xenograft models in SCID mice showed an additive, and possibly a synergistic, effect when combining EnAd (hybrid of two group B adenoviruses-Ad3 and Ad11p) with low-dosage radiation.…”
mentioning
confidence: 97%
“…Because numerous Ad proteins, and especially E4 proteins, contribute to inhibition of the DDR and, therefore, sensitize cells to the toxic effects of DNA damage, it was suggested that addition of DNA-damaging drugs or irradiation may synergistically augment cancer virotherapy by oncolytic Ads. This hypothesis was confirmed by several studies [ 158 , 159 , 160 ]. In such studies, utilization of many different Ad vectors in various cell types as well as in tumor xenografts, demonstrated that a combination of Ad infection and DNA damage induced by drugs or irradiation was significantly more toxic than either treatment alone [ 160 , 161 , 162 , 163 ].…”
Section: Dna Damage and Oncolytic Adssupporting
confidence: 78%
“…This hypothesis was confirmed by several studies [ 158 , 159 , 160 ]. In such studies, utilization of many different Ad vectors in various cell types as well as in tumor xenografts, demonstrated that a combination of Ad infection and DNA damage induced by drugs or irradiation was significantly more toxic than either treatment alone [ 160 , 161 , 162 , 163 ]. Moreover, DDR inhibition by drugs also enhanced the impact of oncolytic viruses in tumor cells [ 158 , 159 ].…”
Section: Dna Damage and Oncolytic Adssupporting
confidence: 78%
“…Prodrugs and radiation therapy were also being investigated in combination with OV; and there is clinical data supporting these concepts. [27][28][29] The use of chemotherapy may be a reflection of the tumors being studied and indeed the most common regimens were not specified with the selection of the chemotherapy left to investigator choice or carboplatin/paclitaxel regimens, commonly used in studies of patients with non-small cell lung cancer. Chemotherapy administration did appear to be associated with expected adverse events but it did not appear to be significantly worse with associated OV treatment.…”
Section: Discussionmentioning
confidence: 99%